Human and Animal Minds: Peter Carruthers (2019). Human and animal minds: The consciousness questions laid to rest. Oxford University Press. - Crelier, Andrés; Marte, Fernando (Analysis. Journal of Philosophical Research, 2021)
The review puts forward the central theses of Peter Carruthers in Human and animal minds: The consciousness questions laid to rest (Oxford University Press, 2019). At the same time, it proposes a critical examination of some of his arguments regarding phenomenal consciousness.